Shifting Security Paradigm in Contemporary Era: Role of Law Enforcement Agencies - Pandit, Sudip (Journal of APF Command and Staff College, 2019)
In setting of today’s security challenges, striving for sound policing of military character through paramilitary, auxiliary and armed police forces has usurped. The law enforcement agencies are engaged to curb the security threats at realm of dynamic security challenges. The changing perspectives of security scenario along with modern security challenges like terrorism, out and in migration, armed activities and actions of non-state actors are very common to states. The security challenges due to the increase in terrorism, extremism, armed conflict, insurgency, civil war, cyber threats, and non-state actor’s activities, are some of the looming security concerns affecting effectiveness and efficacy of the law enforcement agencies. This research is conducted by applying descriptive research method and secondary sources to identify the perspectives of modern-day security situation and role of law enforcement agencies to combat these challenges. This paper highlights the contemporary security challenges contextualized at the global realm to offer possible future strategies in general for the security agencies within and outside the country.